Qualitative Analysis of the Implementation of Inquiry-Based Physics Learning Tools on Strengthening Character and Improving Learning Outcomes - Sari, Silvina Anjar; Oransa, Mohamed A (Schrödinger: Journal of Physics Education, 2025)
Purpose of the study: This study aims to analyze the implementation of inquiry-based physics learning devices to support character strengthening and improve student learning outcomes.Methodology: This study uses a qualitative approach with a case study design. The subjects of the study were students and teachers of grade XI majoring in natural sciences 2 of Sleman 2 State Senior High School, selected using purposive sampling technique. Data were collected through observation, interviews, and document analysis. Data analysis used the Miles and Huberman model with data reduction, data display, and drawing conclusions through triangulation.Main Findings: Inquiry-based learning increases students' active engagement, understanding of physics concepts, and critical thinking skills. Students are more independent, creative, and demonstrate positive character traits such as honesty, discipline, and cooperation. Test results show significant improvements in academic achievement. This approach is effective in supporting character building and the development of 21st-century skills according to the Merdeka Curriculum.Novelty/Originality of this study: This study reveals the effectiveness of inquiry-based physics learning devices not only in improving learning outcomes, but also in building students' character. This study provides new insights into the integration of character building in physics learning, in line with the Merdeka Curriculum, and shows how the inquiry approach can develop 21st century skills more holistically.